Pengawasan Pemerintah Daerah Terhadap Penjualan Rokok Eceran - Lain, Haryani; Nendissa, Renny Heronia; Soplanit, Miracle (Faculty of Law, Universitas Pattimura, 2025)
Retail cigarette sales are one of the factors contributing to the increasing number of smokers, especially among teenagers and children. Although the government has implemented various regulations regarding tobacco control, particularly related to the prohibition of retail cigarette sales, the practice of retail cigarette sales is still widespread due to weak supervision.This research aims to analyze the form of supervision carried out by local governments over the retail sale of cigarettes and the legal consequences if the supervision is not conducted optimally.This writing uses normative legal research type, with an approach to legislation and a conceptual approach.The form of local government supervision over retail cigarette sales is carried out through two main approaches, namely preventive and repressive supervision. Preventive supervision includes socialization, education, and routine inspections, while repressive supervision is conducted after violations occur by imposing administrative or legal sanctions. The government's failure to supervise can lead to various legal consequences, including violations of legislation, an increase in the prevalence of novice smokers, and serious health impacts on the community. The government can be deemed negligent in performing its duties, thus potentially facing legal action. Therefore, it is important for the government to strengthen the supervision and law enforcement systems related to retail cigarette sales to protect public health and ensure compliance with applicable regulations.